Investigation of thermal behaviour, pressure drop, and pumping power in a Cu nanofluid-filled solar flat-plate collector - Shamshirgaran, S.R. (EDP Sciences, 2017)
The evaluations of the performance of solar flat-plate collectors are reported in the literature. A computer program developed by MATLAB has been applied for modelling the performance of a solar collector under steady state laminar conditions. Results demonstrate that Cu-water nanofluid would be capable of boosting the thermal efficiency of the collector by 2.4 at 4 volume concentration in the case of using Cunanofluid instead of just water as the working fluid. It is noteworthy that, dispersing the nanoparticles into the water results in a higher pressure drop and, therefore, a higher power consumption for pumping the nanofluid within the collector. It has been estimated for the collector understudy, that the increase in the pressure drop and pumping power to be around 30. © The authors, published by EDP Sciences, 2017.